Red LED light accelerates capsanthin accumulation and fruit ripening in pre-harvest pepper (Capsicum annuum L.) - Mao, Pengpeng; Yang, Qi; Yang, Tao; Zou, Ping; Zheng, Yinjian (Frontiers in Plant Science, 2025)
As an essential environmental regulator, light plays a crucial role in pre-harvest fruit quality and fruit ripening. However, developing efficient light-based strategies for precise regulation during critical crop growth stages remains a substantial challenge in controlled-environment agriculture. Fruit ripening in pepper (Capsicum annuum L.) is characterized by the development of its distinctive red color, which is primarily driven by the accumulation of capsanthin, a carotenoid that serves as the principal pigment in ripe pepper fruits. Nevertheless, the mechanism by which red LED light regulates capsanthin accumulation, and thus the color change of pepper fruits, remains unclear. In this study, ‘Zunla-1’ pepper fruits at the green ripening stage (30 days after flowering, DAF) were selected for pre-harvest red LED light treatment. Results showed that red LED light significantly promoted the color change of pepper fruits and accelerated capsanthin accumulation compared to white LED light. Additionally, red LED light upregulated the expression of carotenoid biosynthesis genes PSY, LCYB, CRTZ, and CCS at 34 and 38 DAF, with CCS exhibiting the highest expression at 38 DAF. Correspondingly, the concentrations of PSY, LCYB, CRTZ, and CCS enzymes were significantly increased under red LED light from 34 to 46 DAF, indicating that red LED light accelerated capsanthin accumulation more rapidly than white LED light. Virus-induced gene silencing assays confirmed that CCS (Capana06g000615) exhibited a stronger response to red LED light than PSY (Capana04g002519), LCYB (Capana05g000023), and CRTZ (Capana03g002170). Collectively, these findings demonstrate that pre-harvest red LED light accelerates pepper fruit ripening and capsanthin accumulation, and CCS plays a pivotal role in the red LED light-mediated regulatory process. This study provides novel insights into light-regulated fruit ripening and presents potential strategies for optimizing vegetable quality through targeted photobiological interventions.